Analyzing The Factors That Causing AUTO2000 Setiabudi Never Reaches The Unit Entry Target - Mutalib, Abdul; Wandebori, Harimukti (Journal of Business and Management, 2013)
Auto2000 is the biggest authorized dealer that handles the sustainability of Toyota cars in Indonesia. Auto2000 providing the network of sales, and after sales. On March 2012, Auto2000 opened a new branch located on Jl. Dr. Setiabudi, Bandung. Since its opening, the after sales service from this branch, never achieve its monthly customer unit entry target. The purpose of this study is to increase customer retention at after sales service of Auto2000 Setiabudi. The understanding about the theory of marketing strategy, 7ps of marketing mix, service quality, customer satisfaction, and customer loyalty used to solve the occurring problem. The methodology contains of research framework and determining sampling method. Slovin Theory is used in determining the number of samples. Both qualitative and quantitative analysis used in processing the data result on data analysis part. The result from service qualityâ€™s factor analysis has a significant effect towards customer satisfaction and customer satisfaction also has a significant effect toward customer loyalty. The conclusion of this research is that After Sales Division of Auto2000 Setiabudi needs to improve some aspects from its service quality, customer satisfaction, and customer loyalty in accordance to optimizing its unit entry target.Â Keywords : Auto2000, Marketing Strategy, Customer Intention, Service Quality, After Sales